Dementia and Alzheimer's disease incidence in relationship to cardiovascular disease in the Cardiovascular Health Study cohort. - Newman, Anne B; Fitzpatrick, Annette L; Lopez, Oscar; Jackson, Sharon; Lyketsos, Constantine; Jagust, William; Ives, Diane; DeKosky, Steven T; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether coronary artery disease, peripheral arterial disease (PAD), or noninvasive markers of cardiovascular disease (CVD) predict the onset of dementia and Alzheimer's disease (AD). DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Men and women (N=3,602) with a brain magnetic resonance imaging (MRI) scan but no dementia were followed for 5.4 years. Participants with stroke were excluded. MEASUREMENTS: Neurologists and psychiatrists classified incident cases of dementia and subtype using neuropsychological tests, examination, medical records and informant interviews. CVD was defined at the time of the MRI scan. Noninvasive tests of CVD were assessed within 1 year of the MRI. Apolipoprotein E allele status, age, race, sex, education, Mini-Mental State Examination score, and income were assessed as potential confounders. RESULTS: The incidence of dementia was higher in those with prevalent CVD, particularly in the subgroup with PAD. The rate of AD was 34.4 per 1,000 person-years for those with a history of CVD, versus 22.2 per 1,000 person-years without a history of CVD (adjusted hazard ratio (HR)=1.3, 95% confidence interval (CI)=1.0-1.7). Rates of AD were highest in those with PAD (57.4 vs 23.7 per 100 person-years, adjusted HR=2.4, 95% CI=1.4-4.2). Results were similar with further exclusion of those with vascular dementia from the AD group. A gradient of increasing risk was noted with the extent of vascular disease. CONCLUSION: Older adults with CVD other than stroke had a higher risk of dementia and AD than did those without CVD. The risk was highest in people with PAD, suggesting that extensive peripheral atherosclerosis is a risk factor for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Peripheral Vascular Diseases; Risk Factors